Acute impact of cigarette smoking on power spectral measures of HRV - Ferdous, Mehboba; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2018)
Background: Cigarette smoking is associated with various forms of acute cardiac events such as myocardial infarction and ventricular fibrillation etc. Objective: To observe immediate impact of cigarette smoking on power spectral measures of heart rate variability (HRV) in current apparently healthy male regular cigarette smokers. Methods: This study was carried out on 120 apparently healthy male current regular cigarette smoker aged 20-55 years. To watch the intense impacts, data were recorded 5 and 30 min after completing a full stick of cigarette. Power spectral measures of HRV were recorded by a RMS digital polyrite D. Statistical analysis was done by paired sample t test. Results: LF power, LF nu & LF/HF ratio were significantly increased and HF power & HF nu were significantly decreased from their corresponding baseline value just 5 minutes after smoking and returned close to their baseline value after 30 minutes of smoking. Conclusion: The result of the study concludes that acceleration of sympathetic activity with simultaneous withdrawn of cardiovascular vagal adjustment happens quickly in the wake of smoking a cigarette. J Bangladesh Soc Physiol. 2018, June; 13(1): 8-12